2003
DOI: 10.1063/1.1599051
|View full text |Cite
|
Sign up to set email alerts
|

Absorption of terahertz radiation by plasmon modes in a grid-gated double-quantum-well field-effect transistor

Abstract: Graphene based field effect transistor for the detection of ammonia J. Appl. Phys. 112, 064304 (2012) Unipolar behavior of asymmetrically doped strained Si0.5Ge0.5 tunneling field-effect transistors Appl. Phys. Lett. 101, 123501 (2012) Efficient physical-thermal model for thermal effects in AlGaN/GaN high electron mobility transistors Appl. Phys. Lett. 101, 122101 (2012) Light/negative bias stress instabilities in indium gallium zinc oxide thin film transistors explained by creation of a double donorThe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(56 citation statements)
references
References 19 publications
0
54
0
2
Order By: Relevance
“…The latter condition is justified if we allow an edge charge accumulation at the boundaries. The edge charge accumulation was confirmed by direct numerical solution of the Maxwell equations in the grating gated 2D electron channel [46]. With these boundary conditions each individual segment of the stepped plasmonic transmission line is represented by the equivalent TL circuit elements defined in Eq.…”
Section: Tl Theory Of Plasmonic Crystals In Periodic 2d Electronmentioning
confidence: 99%
“…The latter condition is justified if we allow an edge charge accumulation at the boundaries. The edge charge accumulation was confirmed by direct numerical solution of the Maxwell equations in the grating gated 2D electron channel [46]. With these boundary conditions each individual segment of the stepped plasmonic transmission line is represented by the equivalent TL circuit elements defined in Eq.…”
Section: Tl Theory Of Plasmonic Crystals In Periodic 2d Electronmentioning
confidence: 99%
“…This conclusion was confirmed in Refs. [8,9] where it was shown that the resonant peaks in the photoresponse correlate with plasmon resonances in the channel under the grating gate fingers. In this structure, boundary conditions at the opposite edges of the grating gate fingers are symmetric and can not produce signal rectification.…”
Section: Theory Of the DC Photoresponse In The Grating-gated Fetmentioning
confidence: 99%
“…At plasmon resonance with wave vector q the Fourier amplitude q E of the total electric field is enhanced in compared with the external THz . The radiative damping is proportional to the equilibrium 2D electron density and also depends on the coupling of the plasmon mode to the EM radiation [8,11]. Dissipative damping is determined by the mobility and increases with the temperature.…”
Section: Theory Of the DC Photoresponse In The Grating-gated Fetmentioning
confidence: 99%
“…Такое поведение связано со сверхизлучательным характером коллективной плазмонной моды. В режиме плазмонного сверхизлучения радиационное затухание растет пропорционально концентрации носителей заря-да, колеблющихся в коллективной плазмонной моде [14], тогда как диссипативное затухание плазмонов равно 1/2τ [15] и не зависит от концентрации носителей заряда в графене. Поскольку концентрация носите-лей заряда в графене связана с энергией Ферми как N n(p) ∝ E 2 F π 2 V 2 F , где V F = 10 8 см/с -скорость Фер-ми, то радиационное затухание растет пропорционально квадрату энергии Ферми.…”
Section: результаты расчетов и их обсуждениеunclassified